Infodemiological study of COVID-19 related search trends in Brazil (Research, Society and Development, 2022)
After the World Health Organization (WHO) declared the COVID-19 pandemic, searches related to this subject generated an infodemic. In this sense, the infodemiology field allows understanding the population behavior on the internet. The aims of this study were to analyze, through the application Google Trends, the evolution of internet search trends on medicines related to COVID-19 in the Brazilian context and the impact of specific political, healthcare and scientific events that occurred on this trend. Terms (n=52) and events (n=38) between December 8, 2019 and May 31, 2021 were selected according to the purpose of the study and the researchers' prior scientific knowledge. Statistical analysis was applied to assess interest in the selected terms before and after the events, their association with the predictor variable “percentage of first vaccine doses applied” and the influence of the type of event on the search interest. Our results showed an increase in searches for information related to medicines that are part of the “Kit Covid” or “Tratamento Precoce”, as well as “Vacina” and “Vacinas” shortly after the declaration of the COVID-19 pandemic by the WHO. As for drugs approved for the treatment of COVID-19 in Brazil, the search was greater during the first and second waves of COVID-19 and, with the advancement of vaccination, the searches for “ivermectina” and “hidroxicloroquina” decreased. The data presented bring to light the demand for knowledge about medicines by the Brazilian population in a pandemic scenario where having access to information is immediate, but not always reliable.